Arduino‐based slider setup for gas–liquid mass transfer investigations: Experiments and CFD simulations. Issue 6 (29th February 2020) - Krieger, Waldemar; Bayraktar, Evren; Mierka, Otto; Kaiser, Lutz; Dinter, Robin; Hennekes, Julian; Turek, Stefan; Kockmann, Norbert
Abstract: The implementation of traditional sensors is a drawback when investigating mass transfer phenomena within microstructured devices, since they disturb the flow and reactor characteristics. An Arduino based slider setup is developed, which is equipped with a computer‐vision system to track gas–liquid slug flow. This setup is combined with an optical analytical method allowing to compare experimental results against CFD simulations and investigate the entire lifetime of a single liquid slug with high spatial and temporal resolution. Volumetric mass transfer coefficients are measured and compared with data from literature and the mass transfer contribution of the liquid film is discussed.